CT-based analysis of malignant tumor volume and localization: a preliminary study - Cavalcanti,Marcelo Gusmão Paraiso (2004)
The purpose of this study was to correlate 3D-CT (3D computed tomography) volume measurements of malignant tumors with the response to treatment, and to observe bone invasion in these lesions applying a specific imaging protocol. We analyzed 17 individuals with maxillofacial malignant lesions who were submitted to spiral CT (2D-CT). The original data were transferred to an independent workstation using a 3D volume rendering package software, which was used by two examiners to obtain area and volume measurements of the lesions, independently, three times each, prior to and after treatment. The segmentation protocol was applied for the assessment of bone involvement. The difference between imaging and gold standard values was not considered significant (p > 0.05). Regarding bone invasion, three false-negatives were obtained using MPR-CT (multiplanar reconstruction) and no false-negatives were obtained using the 3D segmentation protocol. The use of 3D-CT may be a differential and important factor for expanding options regarding the localization, dimension, and clarification of lesion components.